Colorectal Cancer and Intestinal Protozoan Infections: Prevalence, Risk Factors, and Molecular Confirmation in Western Iran: A Descriptive Case‐Control Study - Alireza Moayyedkazemi; Amal Khudair Khalaf; Sima Nik Khah Behnamiri; Asghar Sepahvand; Neda Niazi; Maryam Sepahvand; Hossein Mahmoudvand (Health Science Reports, 2026)
ABSTRACT Background and Aims Infections are recognized contributors to cancer development. This study aimed to assess the prevalence, socio‐demographic characteristics, and risk factors associated with intestinal protozoan parasites in patients with colorectal cancer (CRC) in Western Iran. Methods This descriptive case‐control study enrolled 174 CRC patients and 174 non‐CRC healthy controls receiving care at general hospitals in Lorestan Province between October 2022 and August 2024. Fresh stool samples were examined using direct smear, Lugol's iodine, formalin‐ether concentration, and permanent staining (Giemsa and Trichrome). Polymerase chain reaction (PCR) was performed on all samples testing positive for Entamoeba species by microscopy. Data were analyzed using χ 2 tests and binary logistic regression (SPSS v26.0); a two‐sided p < 0.05 was considered statistically significant. Results Intestinal protozoan infections were detected in 24/174 (13.8%) CRC patients and 8/174 (4.6%) non‐CRC controls. CRC patients had significantly higher odds of intestinal protozoan infection than non‐CRC controls (OR = 3.32, 95% CI: 1.45–7.61; Fisher's exact p = 0.0047). Among the identified protozoan parasites were Giardia lamblia (15/32, 46.8%), Entamoeba histolytica (6/32, 18.75%), and E. coli (4/32, 12.5%), respectively. Using a PCR assay, all E. histolytica/E. dispar positive samples were confirmed as E. histolytica . Among CRC patients, rural residence, animal contact, agricultural activity, animal husbandry, and consumption of unwashed fruits or vegetables were significantly associated with intestinal protozoan infection (ORs = 2.55–65.46; p < 0.05). No significant associations were observed with demographic, socioeconomic, or behavioral factors among non‐CRC participants. Conclusion This study found a higher prevalence of intestinal protozoan parasites in CRC patients compared to controls, emphasizing the clinical importance of parasitic infections in this population. Routine screening, improved sanitation, and public health interventions are recommended to reduce infection risks. Further research is needed to explore the long‐term impact of these parasites on cancer progression and immune function.